Environmental journalism : reporting on environmental concerns and climate change in India - Poornananda, D. S. (NewDelhi Sage, 2022)
"Environmental Journalism: Reporting on Environmental Concerns and Climate Change in India examines the increase of environmental concerns and its reflection in Indian media, exploring the possibilities of and constraints in covering environmental news. The book discusses major challenges in environmental reportage, such as political and corporate pressures on media houses and threats to journalists. It discusses why environmental reporting is not considered an important 'beat' and reports covering these issues are usually assigned to junior reporters. This book analyses why journalists lack the proper training to report on environmental issues, focusing on the many obstacles to scientific knowledge and specialized training. It draws critical insights from interviews with environmental journalists, activists and specialists, and will be an important read for scholars of not only media studies and environmental studies but also sociology, politics and development studies. Looking at the media's role in framing environmental degradation as a human rights issue, the book argues that the growth of environmental journalism can contribute significantly to global initiatives for saving the planet"--
Environmental concern and the media : from scepticism to cognizance -- Covering the environment : framing of environmental issues in media -- Advocacy in environmental reporting : activism and professional practices -- Pressures on the publishers and journalists : from resistance to acquiescence -- Scientific uncertainties and lack of specialization in environmental reporting -- Building the environmental agenda : the role of sources -- Environment and the media : coverage of the Narmada Movement -- Environment and the media : the media discourse on Kerala--Kodagu floods -- Conclusion : environmental degradation as a human rights issue.
Includes bibliographical references and index.
Keywords: Environmental protection -- India; Environmental degradation -- India; Climatic changes -- India; Mass media and the environment -- India; Mass media and public opinion -- India